Effect of physical exercise on social adaptability of college students: Chain intermediary effect of social-emotional competency and self-esteem - Liu, Yanying; Feng, Qingkun; Tong, Yao; Guo, Kelei (Frontiers in Psychology, 2023)
Objective: To explore the relationship between physical exercise and college students' social adaptability, as well as the mediating role of social-emotional competency and self-esteem. Methods: 1230 college students were investigated by physical exercise questionnaire, social-emotional competency scale, self-esteem scale, and social adaptability scale. Data were analyzed by Pearson correlation analysis, structural equation model test and deviation-corrected percentile Bootstrap method. Results: (1) Physical exercise was positively correlated with social adaptability (r=0.397, p< 0.01), and the direct path of physical exercise on social adaptability was significant (β=0.397, t=15.174, p<0.01). (2) Physical exercise positively predicted social-emotional competency (β=0.399, t=15.235, p<0.01) and self-esteem (β=0.305, t=10.570, p<0.01). Social-emotional competency positively predicted self-esteem (β=0.130, t=4.507, p<0.01) and social adaptability (β=0.169, t= 6.104, p<0.01). Self-esteem positively predicted social adaptability (β=0.189, t=6.957, p<0.01). (3) Social-emotional competency and self-esteem play a significant mediating role between physical exercise and social adaptability. The mediating effect includes three paths: physical exercise→social-emotional competency→social adaptability (the mediating effect value: 0.068); physical exercise→self-esteem→social adaptability (the mediating effect value: 0.059). Physical exercise→social-emotional competency→self-esteem→social adaptability(the mediating effect value: 0.010). Conclusion: Physical exercise can not only directly affect social adaptability of college students, but also indirectly affect social adaptability through the independent intermediary role of social-emotional competency and self-esteem. Furthermore, physical exercise also affect social adaptability through the chain mediation of social-emotional competency and self-esteem.